IMPACT OF UZBEK LANGUAGE STRUCTURE ON ENGLISH GRAMMAR ACQUISITION - Masrurova Kamolaxon; Ergashev Rasulbek (Galaxy International Interdisciplinary Research Journal, 2024)
Language acquisition, a multifaceted process shaped by linguistic diversity, cognitive mechanisms, and socio-cultural factors, is investigated in this study with a focus on English grammar acquisition among Uzbek learners. The analysis delves into the intricate dynamics influenced by Uzbek language structures, examining syntactic features, verb morphology, and pluralization patterns. The research uncovers nuanced challenges in mastering English grammar, revealing disparities between Uzbek and English syntactic structures, necessitating cognitive adaptation. English verb morphology complexity poses hurdles in tense forms and auxiliary usage, while pluralization patterns and phonological distinctions present additional challenges. Tailored instructional strategies, linguistic support, and cultural immersion experiences are highlighted as crucial for English language development among Uzbek learners. The findings emphasize the need for inclusive pedagogical practices, fostering cross-cultural understanding and advocating for linguistic diversity in education. This research contributes to the discourse on language acquisition, pedagogy, cultural understanding, and educational policy, promoting inclusive learning environments that nurture linguistic growth and intercultural competence in the pursuit of a more interconnected and harmonious world.